2006
DOI: 10.1523/jneurosci.2786-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Changes during Performance of Overlearned Arbitrary Visuomotor Associations

Abstract: The posterior parietal cortex (PPC) is known to be involved in the control of automatic movements that are spatially guided, such as grasping an apple. We considered whether the PPC might also contribute to the performance of visuomotor associations in which stimuli and responses are linked arbitrarily, such as producing a certain sound for a typographical character when reading aloud or pressing pedals according to the color of a traffic light when driving a motor vehicle. The PPC does not appear to be necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 67 publications
8
102
0
Order By: Relevance
“…The latter would be required to explain the direct projection of context information (presumably from PFC) to the hidden layer (presumably PPC) in network I and hybrid network. Alternatively, in highly trained subjects, the direct context input to PPC might be mediated independent from PFC via sensory areas (Grol et al, 2006). This processing scheme would also be compatible with the architecture of either network I or the hybrid network (the source of the context signal being sensory rather than prefrontal areas).…”
Section: Anatomical-physiological Interpretations Of the Network Connmentioning
confidence: 78%
“…The latter would be required to explain the direct projection of context information (presumably from PFC) to the hidden layer (presumably PPC) in network I and hybrid network. Alternatively, in highly trained subjects, the direct context input to PPC might be mediated independent from PFC via sensory areas (Grol et al, 2006). This processing scheme would also be compatible with the architecture of either network I or the hybrid network (the source of the context signal being sensory rather than prefrontal areas).…”
Section: Anatomical-physiological Interpretations Of the Network Connmentioning
confidence: 78%
“…We found that LIP neurons also responded robustly in this task, simultaneously encoding the location of the cue and the active limb. This suggests that parietal association areas are instrumental for linking relevant visuospatial and motor variables, not only for goal-directed but also for symbolically cued behaviors (Toth and Assad, 2002;Grol et al, 2006). Selectivity for cue location was the primary and most prevalent signal in the LIP, because strong cue-evoked activity was found in the vast majority of neurons and correlated with behavioral reaction time mainly independently of the active limb.…”
Section: Discussionmentioning
confidence: 99%
“…Dual-task paradigms have been consistently used as rigorous tests of automaticity (Passingham, 1996;Oliveira et al, 1998;Poldrack et al, 2005;Grol et al, 2006). We assessed the level of automaticity attained in both conditions to determine the robustness of performance to distractors.…”
Section: Taskmentioning
confidence: 99%